2005
DOI: 10.1080/15227950500503660
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and Ultrastructure of Human Umbilical Blood Vessels

Abstract: To resolve controversy over umbilical vessels structure, a morphological review was undertaken of the histology of blood vessels in 130 fetal umbilical cords varying in gestational age and the ultrastructure of blood vessels in 6 umbilical cords. Arteries and veins were lined by endothelium. The internal elastic lamina was frequently interrupted when associated with intimal thickening of longitudinally orientated smooth muscle cells. Fragments of elastic laminae developed in the intima and inner media both of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Endothelial injury and damage was most observed at the 16 th gestational week. Stehbens et al [10] in their histological study of human UVs observed cell debris in the walls of umbilical vessels that could be attributed to hemodynamic stress of the fetoplacental circulation resembling early events of atherogenesis. Lu and Kassab, [15] stated that the vascular walls are subjected to three hemodynamic forces; the blood pressure created by cardiac contraction, the circumferential stretch of the vessel with the cardiac cycle, and the shear stress.…”
Section: Histomorphometric Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Endothelial injury and damage was most observed at the 16 th gestational week. Stehbens et al [10] in their histological study of human UVs observed cell debris in the walls of umbilical vessels that could be attributed to hemodynamic stress of the fetoplacental circulation resembling early events of atherogenesis. Lu and Kassab, [15] stated that the vascular walls are subjected to three hemodynamic forces; the blood pressure created by cardiac contraction, the circumferential stretch of the vessel with the cardiac cycle, and the shear stress.…”
Section: Histomorphometric Resultsmentioning
confidence: 99%
“…Vascular SMCs the main stromal cells of vascular wall assume structural and physiological functions. It synthesizes the extracellular matrix during development and provide arterial wall with the capacity of withstanding high pressure of circulating blood [10,20] . In addition, the vascular SMCs possess fibroblastic function producing collagen and elastin in the developing media hence collagen content in the vessel wall is a reflection of SMC maturity [8] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is typically composed of two arteries and a vein suspended in a hydrated extracellular matrix known as Wharton's jelly. Two veins are originally present, but the second one usually atrophies during pregnancy [9]. Wharton's jelly mesenchymal stem cells (WJMSCs) are more primitive than those isolated from other tissue sources and do not express the major histocompatibility complex (MHC) class II (HLA-DR) antigens [10].…”
Section: Treatment Of Hep-2 Cell Line With Wharton's Jelly Mesenchymamentioning
confidence: 99%